1985
DOI: 10.1152/jappl.1985.59.6.1902
|View full text |Cite
|
Sign up to set email alerts
|

Influence of menstrual cycle on shivering, skin blood flow, and sweating responses measured at night

Abstract: In 10 women, external cold and heat exposures were performed both in the middle of luteal phase (L) and in the early follicular phase (F) of the menstrual cycle. Serum progesterone concentrations in L and F averaged 46.0 and 0.9 nmol X l-1, respectively. The experiments took place between 3:00 and 4:30 A.M., when the L-F core temperature difference is maximal. At neutral ambient temperature, esophageal (Tes), tympanic (Tty), rectal (Tre), and mean skin (Tsk) temperatures averaged 0.59 degrees C higher in L tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 0 publications
8
94
1
Order By: Relevance
“…This disagreement between earlier studies and the present study may have resulted, in part, from differences in the experimental conditions, including differences in exercise position [Fukuoka et al (14) and Grucza et al (15) exercised their subjects in an upright position], indexes of core body temperature (the earlier studies used rectal temperature), or in the physical characteristics of the subjects. Previous studies have suggested that T es is a better index with which to evaluate heat loss responses than rectal temperature (17,18,28,36). Therefore, our results may be more accurate than those of earlier studies in which rectal temperature was used to evaluate sensitivity of the core temperature (14,15).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This disagreement between earlier studies and the present study may have resulted, in part, from differences in the experimental conditions, including differences in exercise position [Fukuoka et al (14) and Grucza et al (15) exercised their subjects in an upright position], indexes of core body temperature (the earlier studies used rectal temperature), or in the physical characteristics of the subjects. Previous studies have suggested that T es is a better index with which to evaluate heat loss responses than rectal temperature (17,18,28,36). Therefore, our results may be more accurate than those of earlier studies in which rectal temperature was used to evaluate sensitivity of the core temperature (14,15).…”
Section: Discussionmentioning
confidence: 53%
“…thermoregulation; estradiol; progesterone; long-term endurance training; heat acclimatization HEAT LOSS RESPONSES, SUCH as sweating and cutaneous vasodilation, during exercise in women differ from those in men because female hormones modify the responses after puberty (3). All studies of the effects of the menstrual cycle on heat loss responses during exercise have demonstrated that the core body temperature thresholds for sweating and cutaneous vasodilation are higher during the luteal phase of the menstrual cycle than during the follicular phase (14,15,17,18,23,31,33,35). In addition, the rise in the core body temperature threshold for sweating and cutaneous vasodilation during the luteal phase is mainly due to elevated progesterone concentrations (8, 31).…”
mentioning
confidence: 99%
“…Baseline resting esophageal temperature was ϳ0.18°C higher in the LP compared with the FP. Although estrogen and progesterone are known to have varying effects on core body temperature response (53,54), the transient increase in esophageal temperature observed during the LP appears to be related to combined influence of the higher levels of circulating sex hormones, progesterone and estrogen (20,21).…”
Section: Discussionmentioning
confidence: 97%
“…The sample consisted of males, as exercise intensity and duration could be confounded with a co-ed sample (i.e., males vs. females may require a different level of exercise to produce the level of dehydration desired) [13][14][15]. Further, only Caucasian males were utilized, as non-whites and female have demonstrated differences in thermoregulation [16,17]. The study protocol was approved by the Institutional Review Board at Kent State University.…”
Section: Subjectsmentioning
confidence: 99%